2017
DOI: 10.1111/vox.12540
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of MNC and lymphocyte collection settings employing different Spectra Optia® Leukapheresis systems

Abstract: The Spectra Optia CMNC device using lower centrifugal force (PF4·0) showed similar target cell yield and composition as well as collection efficiencies with superior performance parameters and lower PLT contamination compared to the MNC setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
38
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 11 publications
6
38
1
Order By: Relevance
“…But in contrast to our data, the perfect correlation of both variables could not be shown. Regarding the RF values, the values of Punzel et al [10] for WBCs, MNCs, and lymphocytes were nearly twice as high when compared to our values. The same applies to the RF values for CD45+, CD3+ and CD14+ cells presented by Strasser et al 2005 [15] and 2007 [18].…”
Section: Discussioncontrasting
confidence: 59%
See 4 more Smart Citations
“…But in contrast to our data, the perfect correlation of both variables could not be shown. Regarding the RF values, the values of Punzel et al [10] for WBCs, MNCs, and lymphocytes were nearly twice as high when compared to our values. The same applies to the RF values for CD45+, CD3+ and CD14+ cells presented by Strasser et al 2005 [15] and 2007 [18].…”
Section: Discussioncontrasting
confidence: 59%
“…In correspondence with these results, Svensson et al [17] found a strong correlation between the concentrations of monocytes and lymphocytes in the blood pre-apheresis and the number of monocytes and lymphocytes collected. In contrast, Punzel et al [10] detected only a weak correlation between the CD3+ pre-apheresis values and the CD3+ cell yield in the product. Steininger et al [11] could show a significant correlation between the pre-apheresis cell count and the correspondent product cell yield for CD14+ but not for CD3+ cells.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations